Algunos rasgos definitorios de un Derecho del Trabajo en proceso de cambio - Goldin, Adrián O. (2014)
Labor Law is an area of Law that has generated much controversy branch of over the years. This is mainly because this branch of Lawis in constant change and development, to which the system must adapt. Because of the importance of the topic, this article seeks to identify the essential  (defining) features of Labor law, including those features that have been recently defined.What this article tries to accomplish is to identify those defining features of Labor law and to give them a practical utility, and let us be able to monitor a branch of Law that has been constantly changing, and be prepared for its future development.